(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
I propose in this research the analysis of memories and representations (understood as a mechanism by which an individual, or a group of individuals, gives/builds/produces/creates a meaning for the social world) of the city of Feira de Santana of the 1940s, from the oppositions of fictional novels, September at the Fair, by Juarez Bahia, and The Werewolf of Feira de Santana, by Fernando Ramos